Long-Term Impact of Economic Conditions on Auditors' Judgment - He, Xianjie; Kothari, S. P.; Xiao, Tusheng; Zuo, Luo (The Accounting Review, 2018)
ABSTRACT We find that economic conditions at the time an auditor enters the labor market have a long-term impact on her judgment and decision making. Specifically, engagement partners who started their career during economic downturns issue audit adjustments more frequently. For the subsample of company-years with no audit adjustments, downturn auditors are more likely to issue a modified audit opinion. In addition, companies audited by downturn auditors are less likely to violate financial reporting and disclosure regulations. Together, our findings suggest that the early career stage is a critical formative period for auditors. JEL Classifications: J24; M42.